Dispelling Fiscal Illusions : How Much Progress Have Governments Made in Getting Assets and Liabilities on Balance Sheet? - Irwin, Timothy (IMF Working Papers; Working Paper ;, 2016)
When rights and obligations are not recognized as assets and liabilities on a government's balance sheet, the government's deficit can be reduced by selling off-balance-sheet assets or incurring off-balance-sheet liabilities. This paper examines how much progress has been made in recognizing assets and liabilities and thus dispelling the fiscal illusions that such transactions create. Looking at the accounts, government-finance statistics, and long-term fiscal projections produced in 28 advanced economies in the period since 2003, it finds good progress in the recognition of some assets and liabilities, such as accounts payable and simple financial assets, but much less in others, such as civil-service pensions.